Plant Uptake Offsets Silica Release From a Large Arctic Tundra Wildfire - Carey, Joanna C.; Abbott, Benjamin W.; Rocha, Adrian V. (Earth's future, 2019)
Rapid climate change at high latitudes is projected to increase wildfire extent in tundra ecosystems by up to fivefold by the end of the century. Tundra wildfire could alter terrestrial silica (SiO2) cycling by restructuring surface vegetation and by deepening the seasonally thawed active layer. These changes could influence the availability of silica in terrestrial permafrost ecosystems and alter lateral exports to downstream marine waters, where silica is often a limiting nutrient. In this context, we investigated the effects of the largest Arctic tundra fire in recent times on plant and peat amorphous silica content and dissolved silica concentration in streams. Ten years after the fire, vegetation in burned areas had 73% more silica in aboveground biomass compared to adjacent, unburned areas. This increase in plant silica was attributable to significantly higher plant silica concentration in bryophytes and increased prevalence of silica‐rich gramminoids in burned areas. Tundra fire redistributed peat silica, with burned areas containing significantly higher amorphous silica concentrations in the O‐layer, but 29% less silica in peat overall due to shallower peat depth post burn. Despite these dramatic differences in terrestrial silica dynamics, dissolved silica concentration in tributaries draining burned catchments did not differ from unburned catchments, potentially due to the increased uptake by terrestrial vegetation. Together, these results suggest that tundra wildfire enhances terrestrial availability of silica via permafrost degradation and associated weathering, but that changes in lateral silica export may depend on vegetation uptake during the first decade of postwildfire succession. Plain Language Summary Climate change in the Arctic is leading to more frequent and severe wildfire in Arctic tundra ecosystems. Studying the silica (SiO2) cycle in Arctic ecosystems is important because the amount of silica exported from land to sea can control uptake by marine primary producers in Arctic coastal waters. We investigated how tundra wildfire affects silica cycling by returning to a large Arctic wildfire 10 years after the burn to collect samples of stream water, vegetation, and peat. We found that plants growing on burned landscapes contained 73% more silica in their aboveground biomass compared to unburned areas nearby. While the fire thawed permafrost underneath it, we did not observe increased levels of silica in streams draining burned areas. This pattern indicates that elevated rates of silica uptake via plants may prevent increased silica export to marine waters following tundra wildfire. We conclude that the effect of tundra fire on silica cycling depends on the recovery trajectories of terrestrial and aquatic ecosystems in the Arctic. Key Points After the largest Arctic tundra fire in recent times, burned vegetation had 73% more silica in aboveground biomass, due to higher plant silica concentration in bryophytes and increased prevalence of silica‐rich gramminoids in burned areas Wildfire redistributed peat silica stocks, with higher concentrations, but 29% lower total stocks due to shallower peat layer postburn Dissolved silica concentration in tributaries draining burned catchments did not differ from unburned catchments, indicating that accelerated vegetation uptake may limit lateral silica export during the first decade of post wildfire succession